A Model of Trips Route Planning to Improve The Accessibility of Public Transportation In Bengkalis City Using Geographic Information System (GIS) - Jaafar, Nur'ain; Saputra, Hendra; Lisya, Mutia (UI Scholars Hub, 2025)
The increase in population and motorized vehicles in Bengkalis City has led to greater demand for public transportation, which remains insufficient in meeting accessibility needs. This study aims to develop a model for planning public transportation routes using Geographic Information System (GIS) tools to improve accessibility in Bengkalis City. The study employs primary data from field surveys and secondary data from relevant agencies. GIS-based spatial analysis methods, such as service area analysis and the Origin-Destination (OD) matrix, are applied to evaluate accessibility and passenger movement patterns. The analysis results in two route alternatives assessed based on stop point density, community accessibility, and passenger distribution. The first alternative is identified as more effective in serving population centers and minimizing service gaps. The findings provide a spatially grounded approach to transportation planning and may support local efforts to improve public transport coverage.